2019
DOI: 10.1080/16078454.2019.1590965
|View full text |Cite
|
Sign up to set email alerts
|

Soluble programmed death-ligand 1 are highly expressed in peripheral T-cell lymphoma: a biomarker for prognosis

Abstract: Purpose: To investigate the role of soluble programmed cell death ligand 1 (sPD-L1) protein in plasma of patients with Peripheral T-cell lymphoma (PTCL). Methods: In total, 80 patients with newly diagnosed PTCL and 75 healthy controls were enrolled. Levels of sPD-L1 were measured by ELISA at diagnosis and after 3-8 courses of chemotherapy. The expression of PD-L1 in tumor tissues from nine PTCL patients was also detected. Results: sPD-L1 was higher in PTCL patients at diagnosis compared to healthy subjects (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
2
21
2
Order By: Relevance
“…Ki-67 has been validated as a marker of proliferation in the initial phase of adult neurogenesis and is used clinically to assess tumor cell proliferative activity in diverse tumor types (49). Although the mechanistic link remains unclear, we suggest that sPD-L1 represents the PD-L1 expression in tumor tissue (25), which is accompanied by suppression of the immune response. In addition, the soluble form of PD-L1 is biologically activated in compromised antitumor immune responses (19).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Ki-67 has been validated as a marker of proliferation in the initial phase of adult neurogenesis and is used clinically to assess tumor cell proliferative activity in diverse tumor types (49). Although the mechanistic link remains unclear, we suggest that sPD-L1 represents the PD-L1 expression in tumor tissue (25), which is accompanied by suppression of the immune response. In addition, the soluble form of PD-L1 is biologically activated in compromised antitumor immune responses (19).…”
Section: Discussionmentioning
confidence: 82%
“…Recently, a few published reports have shown that sPD-L1 is an indispensable predictor in various types of cancer (20)(21)(22), especially for checkpoint blockade treatments (23,24). In addition, some studies have referred to circulating sPD-L1 as a surrogate marker for tumor PD-L1 expression (25). Given that both sPD-L1 and the previously mentioned blood markers have been regarded as indicators of the host immune state (21), we were interested in determining the associations between sPD-L1 measurements and peripheral blood markers in gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…Our secondary hypothesis that sPD‐L1 levels may serve as a biomarker of clinical response was not statistically proven, but a favorable OS trend for those with lower sPD‐L1 expression was noted in the performed post‐hoc analysis. These results suggest that in PCa, high sPD‐L1 expression may correlate with poor prognosis, as observed in various other cancers including lung cancer, 37 gastric cancer, 38–40 rectal cancer, 41 lymphoma, 37,42 renal cell carcinoma, hepatocellular carcinoma, 43 esophageal cancer, 44,45 and soft tissue sarcoma 46 . However, this is the first time that sPD‐L1 is studied in PCa.…”
Section: Discussionmentioning
confidence: 73%
“…Finally, 31 studies involving 17 tumors and a total of 3,780 patients met our inclusion criteria ( Figure 1 ). The tumor types included in the study were; Nasopharyngeal Carcinoma ( 11 ), Cholangiocarcinoma ( 12 ), lung cancer ( 9 , 10 , 13 17 ), Hepatocellular carcinoma ( 20 , 21 , 39 , 40 ), Thyroid carcinoma ( 22 ), Mesothelioma ( 23 ), Colorectal carcinoma ( 24 , 25 ), NK/T cell lymphoma ( 26 , 27 ), Peripheral T-cell lymphoma ( 28 ), Large B-Cell lymphoma ( 29 , 35 ), Hodgkin lymphoma ( 31 ), Ovarian carcinoma ( 32 ), Soft tissue sarcomas ( 33 ), Renal cell carcinoma ( 7 ), Esophageal carcinoma ( 34 ), Gastric carcinoma ( 4 , 35 ), and Pancreatic adenocarcinoma ( 36 , 41 ).…”
Section: Resultsmentioning
confidence: 99%